2018
DOI: 10.13040/ijpsr.0975-8232.9(7).3036-41
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background:Multiple logistic regression analysis of several metabolic variables between polycystic ovary syndrome and control groups revealed that zinc level was the most important variable to predict polycystic ovarian syndrome. Objective: This study was designed to illustrate the correlation between zinc and copper levels with the biochemical changes associated with polycystic ovary syndrome. Materials and Methods: Twelve women with polycystic ovary syndrome and twelve healthy and normal ovulatory women were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The role of Cu in PCOS is complex and may vary with the phenotype. Several studies have found elevated Cu levels in patients with PCOS [151][152][153][154][155][156][157][158][159][160], while others have found no differences from the control group [161][162][163]. Considering metabolic factors, a significant increase in serum Cu levels was found in both obese and non-obese patients with PCOS compared to healthy subjects [153], and this increase was linked to IR [152,164].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…The role of Cu in PCOS is complex and may vary with the phenotype. Several studies have found elevated Cu levels in patients with PCOS [151][152][153][154][155][156][157][158][159][160], while others have found no differences from the control group [161][162][163]. Considering metabolic factors, a significant increase in serum Cu levels was found in both obese and non-obese patients with PCOS compared to healthy subjects [153], and this increase was linked to IR [152,164].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%